Analysis of Proper Assessment Results on Palm Oil Liquid Waste Management on Water Pollution Control Aspects at PT. XX - Prasetio, Bambang; Mufti, Aulia Annas; Zurfi, Alfian; Utami, Dinda Fajar; Kurnianingtyas, Erlina (Journal of Multidisciplinary Academic, 2024)
The industrial world has developed very quickly in recent year, and this has a direct correlation to the emission or trash created. Of course, environmental pollution cannot occur from created waste or pollutants without management or control measures. The Ministry of Environment and Forestry has an innovation, namely the existence of a company performance rating assessment program in environmental management efforts or often called PROPER. PT Asam Jawa is a company engaged in agro-industry and has been registered as a PROPER participant. According to the results of the PROPER assessment, PT Asam Jawa received a blue rating, which means that the company has complied with applicable laws and regulations. The analysis in this report is carried out by looking at the PROPER assessment report on the Water Pollution Control aspect, interviews, observations and documentation related to Water Pollution Control. After that, primary and secondary data collection is carried out. Data processing analysis is carried out by descriptive analysis, where a comparison is made between the results of monitoring during practical work with applicable regulations. From the results of the report, it shows that PT Asam Jawa is in the Obedient category where the results are shown through the PROPER assessment report card.